Antifertility Activity and Chemical Content of Moringa Oleifera Lam Plant Extract on The Reproductive System of Male and Female White Rats - Munawir Munawir; Titik Sunarni; Opstaria Saptarini (GLOBAL HEALTH SCIENCE GROUP, 2024)
Research shows that Moringa extract possesses anti-fertility effects on the reproductive systems of male and female rats. This study investigates Moringa's active chemical compounds and their impact on reproductive parameters such as sperm concentration, motility, morphology, and seminiferous tubule diameter, along with hormone levels (progesterone, LH, FSH), estrogenic activity, and the estrous cycle. The research, a literature review, compiles findings from quality international (Scopus) and national (SINTA) journals, Translation and proofreading: there are 8 articles that meet the research inclusion criteria, selected within a range from the year 2010 to 2024. Key active compounds identified in Moringa include alkaloids, tannins, flavonoids (kaempferol and quercetin), and benzyl isothiocyanate, all of which demonstrate anti-fertility effects. These compounds were observed to reduce sperm concentration, motility, and morphology, and to decrease seminiferous tubule diameter in males, while also impacting hormone levels and the estrous cycle in females. The findings support Moringa’s potential as an anti-fertility agent, highlighting its impact across various reproductive parameters in both genders.